2009
DOI: 10.1002/da.20507
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of a school-based Internet program for reducing depressive symptoms in adolescent girls

Abstract: Background: This study evaluates the benefits of a self-directed Internet intervention for depression (MoodGYM) delivered as a part of the high school curriculum. Method: One hundred and fifty-seven girls, aged 15 and 16 years, were allocated to undertake either MoodGYM or their usual curriculum. MoodGYM's impact on depressive symptoms, risk of depression, attributional style, depression literacy and attitudes toward depression was examined using random effect regression. Results: MoodGYM produced a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 29 publications
4
152
1
3
Order By: Relevance
“…Therefore, the total number of papers reviewed here is 10, and the characteristics of the included studies are summarised in Tables 1 and 2. Interventions Six studies reported the use of cCBT for symptoms of depression or low mood and described four different programmes. Of these studies, three were intervention trials with children with mild or moderate depression (Gerrits et al 2007;Van Voorhees et al 2008, 2009, two were school-based prevention trials with community samples (O'Kearney et al 2006(O'Kearney et al , 2009 and one studied those with diagnosed depression (Abeles et al 2009). Of the intervention programmes, Abeles et al (2009) All programmes were interactive and multimedia, and included elements such as psychoeducation, exercises and quizzes, home work assignments, case vignettes, narration, cartoons and videos.…”
Section: Identified Via 'Cited By' Update N=0mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the total number of papers reviewed here is 10, and the characteristics of the included studies are summarised in Tables 1 and 2. Interventions Six studies reported the use of cCBT for symptoms of depression or low mood and described four different programmes. Of these studies, three were intervention trials with children with mild or moderate depression (Gerrits et al 2007;Van Voorhees et al 2008, 2009, two were school-based prevention trials with community samples (O'Kearney et al 2006(O'Kearney et al , 2009 and one studied those with diagnosed depression (Abeles et al 2009). Of the intervention programmes, Abeles et al (2009) All programmes were interactive and multimedia, and included elements such as psychoeducation, exercises and quizzes, home work assignments, case vignettes, narration, cartoons and videos.…”
Section: Identified Via 'Cited By' Update N=0mentioning
confidence: 99%
“…Two of these RCTs were anxiety treatment trials (March et al 2009;Spence et al 2006). One, and a subsequent follow-up study, evaluated an intervention for those with sub-clinical depression (Van Voorhees et al 2008, 2009) and two were school-based depression prevention trials (O'Kearney et al 2006(O'Kearney et al , 2009. Sample sizes were often small, but varied considerably with the numbers in cCBT conditions ranging from n = 2 to n = 189.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the complexities associated with delivering a successful internet-delivered intervention for this population are naturally more challenging, with some studies suggesting that severely depressed individuals participate less in iCBT [22] and sometimes demonstrate less improvement than the mild to moderately depressed group [23]. Despite this, iCBT programmes tailored to each individual have been found to produce similar effects for those with severe depression, as those with mild to moderate levels [24], and such findings have also been demonstrated in a younger cohort [22]. Progressing implementation of internet-delivered interventions with severely depressed cohorts has been much slower than in mild to moderately depressed groups, particularly because of the increase risk of suicide associated with this population [25].…”
Section: Internet-delivered Interventionsmentioning
confidence: 99%
“…Fewer evaluations exist of computer-based programs for children and adolescents; however, the literature is expanding. A number of studies exist evaluating the efficacy of computerbased treatments for child anxiety, [65][66][67] selective mutism, [68] specific phobia, [69] disordered eating, [70] and depression [67,[71][72][73] among youth.…”
Section: Computer-based Cognitive-behavioral Treatmentsmentioning
confidence: 99%